Factors Predicting Outcome of Total Thyroidectomy in Young Patients with Multiple Endocrine Neoplasia Type 2: A Nationwide Long-Term Follow-up Study - Schreinemakers, Jennifer M. J. (Springer-Verlag, 2010)
BACKGROUND: Multiple endocrine neoplasia type 2 (MEN 2) is caused by a RET mutation in chromosome 10. All MEN 2 patients develop medullary thyroid carcinoma (MTC). The age-related risk of MTC is associated with the type of RET mutation. Our aim was to identify prognostic factors associated with recurrent MTC in MEN 2 patients. METHODS: In a nationwide case–control study, all patients who underwent total thyroidectomy in the Netherlands under the age of 20 years were classified into standard (1), high (2), or very high risk (3) for MTC based on RET-mutation type. Disease-free patients were compared with those with recurrent disease. RESULTS: A total of 93 patients were included in the study. Sixty-six percent had MTC on histology, the youngest being 1 year old. Codon 634 was most affected. Sixteen (18%) patients had persistent or recurrent disease, one of whom died. Significantly associated determinants of outcome in univariate analysis were higher age at surgery, no age-appropriate prophylactic surgery according to risk level, elevated preoperative calcitonin levels, affected codon, and the presence of lymph node metastases at surgery. On multivariate analysis only age of surgery was the single independent factor associated with persistent disease. CONCLUSIONS: Prophylactic thyroidectomy beyond the recommended age is associated with persistent/recurrent disease. In addition, codon 634 mutation is associated with a high risk of recurrence requiring early surgery for all these patients.